Karakteristik dan Praktik Kepemimpinan Kepala Sekolah Perempuan: Suatu Studi Kualitatif - Rohmatika, Dina (Lembaga Sosial Rumah Indonesia, 2023)
Leadership is a vital element in both formal and non-formal education. Both men and women have equal opportunities and space to become leaders. The success of a school principal is determined by their ability to manage their school effectively. This study employs a descriptive-qualitative approach. To gather data, the researcher conducted interviews with School Principals, Vice Principals for Student Affairs, Vice Principals for Curriculum, and Students. The findings of the study reveal that: (1) Female School Principals exhibit openness in receiving criticism and suggestions from subordinates, demonstrate care for their staff, and display firmness and responsibility in decision-making. (2) In enhancing students' morals and religious values, the School Principal implements notable programs such as Madrasah Al-Qur'an, pre-class recitation, congregational Duha and Dhuhr prayers, school extracurricular activities, and other habitual practices integrated into school activities. (3) The effectiveness of school leadership is examined through two phases: initiating structure (prioritizing goal achievement) and consideration (concern for subordinates). Three interrelated elements, namely leader behavior, subordinate, and situation, synergistically contribute to the realization of effective leadership.